Antimicrobial Activity of Water and Methanol Leaf Extracts of Green Tea (Camellia Sinensis) Against Some Pathogenic Bacteria - Saleh, Shahlaa M; Saleh, Bushra H; A, Enas S Bahjat (Al-Nahrain Journal of Science, 2018)
This study was carried out to investigate the antimicrobial activity of water and methanol leaf extracts of Camillia sinensis against some pathogenic bacteria. Susceptibilities of S. aureus (SR1), S. aureus (SR2), S.typhimurium, E.coli, P. aeruginosa and Proteus to different antibiotics (Ampicillin, Streptomycin, Rifampicin and Neomycin) by disc diffusion test was carried out. Results revealed that S. aureus (SR1), S. aureus (SR2), P.aeruginosa, and S.typhimurium were resistant to Ampicillin and Rifampicin. E. coli was resistant to Ampicillin, Rifampicin and Neomycin while Proteus was resistant to all antibiotics used in this study. Antimicrobial activity of water and methanol leaf extracts of green tea at different concentrations (20,40,60,80 and 100) mg/ml against pathogenic bacteria was tested. Results showed that green tea water and methanol leaf extract showed inhibitory effect against pathogenic bacteria and methanol extract exhibited better antimicrobial effect against Staphylococcus aureus.